Computational modeling of bacteriophage self-assembly during formation of hierarchical structures. Issue 1722 (12th May 2015) - Warner, Christopher M; Isayev, Olexandr; Poda, Aimee R.; Cuddy, Michael F.; Hodo, Wayne D; Lee, Seung-Wuk; Perkins, Edward J
ABSTRACT: Designing new materials with well-defined structures and desired functions is a challenge in materials science, especially with nanomaterials. Nature, however, solves design of these materials through a self-assembling, hierarchically ordered process. We have investigated the mechanisms by which the high- aspect ratio and unique surface chemistry of M13 bacteriophage can give rise to increasingly complex, hierarchically ordered, bundled phage structures with a wide range of material applications. A molecular dynamic simulation of the 3-D structure of a 20-nm section of wild type (WT) and mutant phage types were developed based on WT phage crystal structure and ab initio calculations. Simulations of these phage were then used to examine repulsive and attractive forces of the particles in solution. Examination of contact interactions between two WT phage indicated the phage were maximally attracted to each other in a head to tail orientation. A mutant phage (4E) with a higher negative surface charge relative to WT phage also preferentially ordered head to tail in solution. In contrast, a mutant phage (CLP8) with a net positive surface charge had minimal repulsion in a 90° orientation. Understanding the self-assembly process through molecular dynamic simulations and decomposition of fundamental forces driving inter- and intra-strand interactions has provided a qualitative assessment of mechanisms that lead to hierarchical phage bundle structures. Results from simulation agree with experimentally observed patterns from self-assembly. We anticipate using this system to further investigate development of hierarchical structures not only from biological molecules but also from synthetic materials.